Long term follow-up of bifurcation aneurysms treated with braided stent assisted coiling and complex T- and Y- stent constructs. (29th September 2017) - Cheung, Nicholas K; Chiu, Albert HY; Cheung, Andrew; Wenderoth, Jason D
Abstract : Background: Stent assisted coil embolization (SACE) of bifurcation aneurysms is challenging. Heterogeneous results have been achieved to date, but largely for laser cut stents. While braided stents offer multiple technical advantages, their long term efficacy has yet to be validated. Objective: To report the first long term 18 month results for the durability of bifurcation aneurysms treated with braided stents. Materials and methods: Over a 4 year period, 59 consecutive patients with 60 bifurcation aneurysms underwent elective braided SACE across three Australian neurovascular centers. 17 of these aneurysms underwent T- or Y-shaped stent constructs. All patients had immediate, 6 month and 18 month clinical and radiological follow-up. Radiological assessment was made on modified Raymond–Roy occlusion scores while clinical assessment was based on the modified Rankin Scale. Subgroup analysis of 17 aneurysms treated with multi-stent constructs was conducted. Results: 6 month follow-up data were available for 59 aneurysms and 18 month follow-up data for 58 aneurysms. Satisfactory aneurysm occlusion was achieved in 97% at inception and at 6 months, and 98% at 18 months. Good neurological outcomes were achieved in 95% at 18 months. Similar satisfactory results were achieved with the multi-stent construct cohort. Intraprocedural thromboembolic events were recorded in 5% and delayed events in 2%. Technical complications were found in 5%. All complication rate was 13%. Conclusion: Braided SACE was safe, efficacious, and durable at the long term 18 month follow-up, including for multi-stent constructs. Preliminary results indicate favorable clinical and radiological outcomes compared with laser cut stents.